Improvement of Thermotolerance of Zymomonas mobilis by Genes for Reactive Oxygen Species-Scavenging Enzymes and Heat Shock Proteins - Anggarini, Sakunda; Murata, Masayuki; Kido, Keisuke; Kosaka, Tomoyuki; Sootsuwan, Kaewta; Thanonkeo, Pornthap; Yamada, Mamoru (Frontiers in Microbiology, 2020)
Thermotolerant genes, which are essential for survival at a high temperature, have been identified in three mesophilic microbes including Zymomonas mobilis. Contrary to expectation, they include only a limited number of genes for reactive oxygen species (ROS)-scavenging enzymes and heat-shock proteins, which are assumed to play key roles at a critical high temperature (CHT) as an upper limit of survival. We thus examined the effects of increased expression of these genes on cell growth of Z. mobilis strains at its CHT. When overexpressed, most of the genes increased the CHT by about one degree and some of them enhanced tolerance against acetic acid. These findings suggest that ROS or unfolded proteins that prevent cell growth are accumulated in cells at the CHT.